Peran Pondok Pesantren Dalam Membentuk Moral Generasi Z di Pekalongan - Ana Chonitsa; Muhammad Mufid; Razie Bin Nasarruddin (IAIN Manado, 2022)
The Role of Islamic Boarding Schools in Shaping Generation Z's Morals In Pekalongan. This article aims to analyze the role and values of Islamic boarding schools in the traditions carried out in Islamic boarding schools as a solution to the problems of Generation Z regarding their morals, manners and morals which are fading and disappearing in the era of globalization. This research is a qualitative research. The informants in this study were caregivers, Mu'alim, and students at the Al-Uthmani Islamic Boarding School. Methods of data collection using interviews, observation and documentation. The results showed that the role of Islamic boarding schools in shaping generation Z had three dimensions, namely the divinity dimension (hablum minallah), the human dimension (hablum minannas), and the natural environment dimension (hablum minal 'alam). These dimensions are formed from the traditions and customs that exist in Islamic boarding schools. The cottage tradition has its own value that can shape the character of the santri so that the pesantren becomes the best consideration and solution for the guardians of the santri to choose the best education in the era of digitalization with clear educational achievements in the formation of good morals.